Virtual reality as a solution: Meeting the needs of deaf students with digital sign language interpreters - Gunarhadi; Wiliyanto, Dian Atnantomi; Anggarani, Fadjri Kirana; Anggrellangi, Arsy (Edelweiss Applied Science and Technology, 2024)
Sign language is the primary means of communication for people who are deaf or hard of hearing. Sign language interpreters help support deaf individuals in understanding lecture material in class. This study aimed to analyze the need for digital sign language interpreters based on Virtual Reality for deaf students' lectures. This online survey-based study via Google form examined the perceptions and needs of digital sign language interpreters based on virtual reality for deaf student lectures. Participants in this study consisted of 51.5% (male) and 48.5% (female) deaf students from various public and private universities in Indonesia. The results of a survey conducted on 200 deaf students about their interest in using VR showed that 64% (128 students) were in the agreed category. The primary need in lectures for deaf students is a sign language interpreter. The results of a study conducted via the Google form showed that 80% or as many as 160 out of 200 students agreed that they needed sign language interpreters to make it easier for deaf students in the lecture process. The study’s results on the perception of the needs of VR and sign language interpreters provide a basis for developing assistive technologies by combining these elements. This will make it easier for deaf students, who are greatly helped by visual media. VR, which can be integrated to display sign language for deaf students, will make explaining the lecturer’s lecture material in class easier.